Molecular detection and clinical characteristics of Bartonella bacilliformis, Leptospira spp., and Rickettsia spp. in the Southeastern Peruvian Amazon basin - Ricapa-Antay F. (2018)
Acute febrile illness (AFI) represent a significant health challenge in the Peruvian Amazon basin population due to their diverse etiologies and the unavailability of specific on-site diagnostic methods, resulting in underreporting of cases. In Peru, one of the most endemic regions to dengue and leptospirosis is Madre de Dios, a region also endemic to emergent bacterial etiologic agents of AFI, such as bartonellosis and rickettsiosis, whose prevalence is usually underreported.We aimed to molecularly identify the presence of Leptospira spp., Bartonella bacilliformis, and Rickettsia spp. by Polymerase Chain Reaction in serum samples from patients with AFI from Puerto Maldonado-Madre de Dios in Peru.